Synchronization In Enforcement Of The Transportation Of Online Motorcycle Taxi Passengers (Ojek Online) - Solechan Solechan (Administrative Law and Governance Journal, 2020)
Abstract Of the several regulatory products that have been enacted there are overlaps and even there are asynchronies between the regulations with one another. This can be seen from the enactment of the Minister of Transportation Regulation No. PM 18 in 2020 and Jakarta Governor Regulation No 33 in 2020. In the governor regulation, large-scale social limitation is regulated. According to the governor's regulation, one of the restricted sectors is the two-wheeled vehicle transportation sector where passenger transportation by motorcycle taxi is only applied to goods. On the contrary in the regulation, online motorbike transportation can be for passengers as long as they follow the health protocol. This has caused confusion in the community and also for law enforcement officials. Keywords: Synchronization, Disharmony, inconsistency, transportation Abstrak Dari beberapa produk peraturan yang sudah diberlakukan saat bencana  terdapat tumpang tindih bahkan terdapat ketidaksinkronan antara peraturan satu dengan yang lain. Hal ini dapat dilihat dari diberlakukannya Peraturan Menteri Perhubungan No. PM 18 tahun 2020 dan Peraturan Gubernur Jakarta No 33 tahun 2020. Menurut peraturan gubernur, salah satu sektor yang dibatasi saat  Pembatasan Sosial Berskala Besar (PSBB)  adalah sektor transportasi kendaraan roda dua dimana pengangkutan penumpang dengan motorcycle taxi hanya diberlakukan untuk barang saja. Sebaliknya dalam permenhub, angkutan ojek online boleh untuk penumpang asalkan mengikuti protokol kesehatan. Hal ini menimbulkan kebingungan di masyarakat dan juga bagi aparatur penegak hukum. Kata Kunci: Sinkronisasi, Disharmonisasi, Inkonsistensi, Transportasi